Primary Intracranial Ewing Sarcoma/Peripheral Primitive Neuroectodermal Tumor Mimicking Meningioma: A Case Report and Literature Review - Jiang, Yining; Zhao, Liyan; Wang, Yubo; Liu, Xinrui; Wu, Xinmin; Li, Yunqian (Frontiers in Oncology, 2020)
ABSTRACT Background: Primary intracranial Ewing sarcoma (ES)/peripheral primitive neuroectodermal tumors (pPNETs) are extremely rare malignancies, which arise in children and adolescents, with only 9 cases reported in patients over 30 years of age. Due to its rarity, MRI features and treatment strategies for primary intracranial ES/pPNETs remain unclear. The purpose of this study was to explore the clinical features, imaging findings, pathological characteristics, different diagnoses, treatment, and prognosis of cerebellar liponeurocytoma in adults. Case description: A 55-year-old female was admitted to the hospital with memory decline over one month, which aggravated in the last 2 weeks. MRI showed a 4.3 cm × 6.5 cm × 3.5 cm heterogeneous large mass in the left frontal lobe with mild peritumoral edema. The mass was successfully removed under neuronavigation and electrophysiological monitoring. The entire mass was removed, and postoperative pathology indicated an ES pPNET diagnosis, with an EWSR1 gene rearrangement. Subsequently, the patient underwent disciplinary radiotherapy. Conclusion: The diagnosis of primary intracranial ES/pPNETs depends on the comprehensive consideration of histological examination, immunohistochemical analysis, and genetic detection. Gross tumor resection combined with radiotherapy and chemotherapy might be the most beneficial treatment.